Two new species of the subfamily Xyleninae from China (Lepidoptera, Noctuidae) - Kononenko, Vladimir (Zootaxa, 2009)
Two new noctuids in the subfamily Xyleninae, Chasminodes behouneki sp. n. and Lithophane gansuana sp. n., belonging to the tribes Cosmiini and Xylenini respectively, are described from central China. The new species C. behouneki and L. gansuana represent allopatric sister species of C. ussurica Kononenko, 1982 and L. pacifica Kononenko, 1978, both described from the Russian Far East. Adults and the genitalia of the species are illustrated, and new distributional data and maps for C. ussurica and L. pacifica are presented. A checklist of the genus Chasminodes is provided.